Re-design and rehabilitation of Ein Deir Baha road - AL-Ashhab, Kareem (جامعة بوليتكنك فلسطين - بنية تحتية, 2021)
منطقة الجلدة بالتحدید )عین دیر بحة( ھي منطقة تقع غرب مدینة الخلیل وھي منطقة تمتاز بأن النمو السكاني في ازدیاد مستمر ، والشارع الذي یخدم المنطقة والمسمى باسمھا )شارع عین دیر بحة( له أھمیة كبیرة تكمن في أنه یربط بین منطقة الجلدة وقریة تفوح في مدینة الخلیل ، أیضا له أھمیة كبیرة حیث أنه یخدم مجموعة من الضواحي، لذا ال بد من الوقوف العادة تصمیم وتأھیل ھذا الشارع لمدى اھمیته على الواطنین . مجاالً للتوسع السكاني والسیاحة الداخلیة واالستجمام تتلخص اھمیة ھذا الطریق انه یعتبر ضمن منطقة تشكل ویخدم العدید من االراضي المتواجدة على ھذا الطریق . یشمل المشروع تصمیم الطریق على تنفیذ اعمال المساحة الالزمة باالضافة الى تصمیم الطریق ھندسیا وانشائیا وكذلك متطلبات تصمیم الطریق من حسابات الكمیات من حفر وردم وتصریف میاه االمطار وغیرھا مع مراعاة قواعد االمان والسالمة لمستخدمي الطریق من مشاة ومركبات . .المساحات والحجوم ,عناصر الطريق ,االنارة ,التأهيل ,اعادة تصميم :K Al-Jaladah area in particular (Ain Deir Baha) is an area located west of the city of Hebron, which is characterized by the fact that the population growth is constantly increasing. Hebron, too, is of great importance as it serves a group of suburbs, so it is necessary to stop to re-design and rehabilitate this street because of its .importance to the citizens The importance of this road is that it is considered within an area that constitutes an area for population expansion, internal tourism and recreation, and serves many .of the lands located on this road The project includes the design of the road to implement the necessary space works in addition to the engineering and construction design of the road, as well as the requirements for the design of the road from the calculations of quantities such as digging, backfilling, rainwater drainage and others, taking into account the safety and security rules for road users, including pedestrians and vehicles. Key Words : Re-Design, Rehabilitation, Lighting on the road, road elements, Areas and volumes .
CD, no of pages 111, بنية تحتية 1/2021
Keywords: roads - Re-design and rehabilitation